A Proposal To Improve Depot Cikampek Social Performance Under Operational Cooperation (KSO) PT Pertamina Patra Niaga As an Effort in Achieving Sustainable Development Performance - Satya, Healthias; Rudito, Bambang (The Indonesian Journal of Business Administration, 2012)
Pertamina’s performance in fuel distribution has been judged incompetent in serving fuel stations. Fuel distribution performance degradation can be seen from the fuel stations complaints about the delivery delays, the inaccuracy number of fuel delivered, and poor quality of fuel delivered. There are several issues that cause this, one of them is Depot Cikampek social performance imbalance performance due to the low level of employees’ trust, sense of belonging, communication, and engagement as indicated by: fuel tanker fleets protest, boycott and fraudulent behavior, and others employees disorderly. Pertamina Patra Niaga as a holder of Pertamina’s depots Operational Cooperation/Kerja Sama Operasi (KSO) agreement has responsibility to the situation.In order to always meet national energy needs, Pertamina and the entire business line include Depot Cikampek required to achieve sustainable development. Using Good Corporate Governance (GCG) as a universal structures and processes for the direction and control of companies that moves towards sustainable development can be found the root causes that causes an imbalance in Depot Cikampek social performance due to the low level of employees’ trust, sense of belonging, communication, and engagement. Root causes analysis conducted through qualitative in-depth interviews with relevant parties by comparing the ideal condition with the actual condition in depot.Based on the analysis, the root cause of the problem found is lack of Good Corporate (GCG) principles implementation as indicated by many provisions of those principles that are not well implemented in Depot Cikampek. Good Corporate (GCG) principles that are not well implemented are the provisions in GCG principles: Transparency, Accountability, Responsibility, and Fairness. Based on the existing root causes, there are several proposed solutions that recommended improving Depot Cikampek social performance in order to achieve sustainable development. The proposed solutions are: generate Global Reporting Initiative (GRI) sustainability reporting that publicly reported; generate the stakeholder engagement; implement Knowledge management system; develop, embedded, and integrate human rights policies in Depot Cikampek business management; and finally establish the public affair management as part of organization structure. Those solution aims to increase employees’ engagement, sense of belonging, and level of trust to the depot management that can improve Depot Cikampek social performance. Keywords: Good Corporate Governance (GCG), Fuel Depot Cikampek, Pertamina Patra Niaga, social performance, sustainable development, company governance, sustainability reporting, Global Reporting Initiative (GRI).